Budget Impact of Rivaroxaban for the Prevention of Thromboembolic Events after Hip or Knee Replacement in Spain - Xavier Granero Xiberta; Antonio Murcia; José Ricardo Troncoso Durán; Claudio Gómez Zubeldia; Aleix Llorac Moix; Ruth Graefenhain De Codes; Maria Giovana Ferrario; Luis Lizán (Journal of Health Economics and Outcomes Research)
**Background:** Anti-thrombotic prophylaxis is routinely used in patients undergoing elective total hip or knee replacement (THR or TKR) to reduce the risk of venous thromboembolism (VTE). In Spain, pharmacological prophylaxis is performed with low-molecular-weight heparin, enoxaparin being the most commonly used. Rivaroxaban is an oral antithrombotic drug that has shown superior efficacy and similar safety profile compared to enoxaparin regimens in randomized clinical trials. The aim of the study was to estimate the budget impact of increasing the use of rivaroxaban with respect to enoxaparin in the prophylaxis of VTE in patients undergoing elective THR or TKR.